The Acts And Resolves, Public And Private, Of The Province Of The Massachusetts Bay Page 268, Image 298 (1869) § 3 - (:unkn) unknown (General Publisher, 1697)
That no person or persons whatsoever, in any town or garrison, shall presume to discharge or shoot off any gun or guns after the shutting in of the daylight in the evening, or before daylight in the morning, unless in case of alarm, approach of the enemy, or other necessary defense, on pain that every person so offending, and being thereof convicted before one or more of his majestie’s justices of the peace, shall forfeit and pay the sum of ten shillings, one moiety thereof to and for the use of the poor of the town where the offence is committed, and the other moiety to him or them that shall inform or prosecute for the same. And in case such offender shall not have wherewith to answer the said fine, or shall refuse or neglect to pay the same, then to be set in the stocks, not exceeding two hours’ time: provided, that this act shall remain and continue in force during the present war, and no longer.
--
Keywords: DISCHARGE